1998
DOI: 10.1042/bj3350697
|View full text |Cite
|
Sign up to set email alerts
|

De novo expression of glutamine synthetase during transformation of hepatic stellate cells into myofibroblast-like cells

Abstract: The expression of glutamine synthetase (GS) was studied in cultured quiescent hepatic stellate cells (HSC) and during their transformation into myofibroblast-like cells. GS mRNA was detectable in quiescent HSC (1-day culture); however, the enzyme protein was not expressed, as assessed by Western blot analysis, immunocytochemistry and the absence of detectable enzyme activity. Similar findings were obtained after 2 days of culture; in addition, the mRNA levels had dropped by about 70%, but they increased again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Hence, providing the first indication that ammonia-induced dysfunction of HSCs is reversible. In accordance with prior observations in rat HSCs [17], human HSCs also express GS. Interestingly, although GS gene expression remained unaffected by increasing concentrations of ammonia, a significant reduction in protein levels was observed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, providing the first indication that ammonia-induced dysfunction of HSCs is reversible. In accordance with prior observations in rat HSCs [17], human HSCs also express GS. Interestingly, although GS gene expression remained unaffected by increasing concentrations of ammonia, a significant reduction in protein levels was observed.…”
Section: Discussionsupporting
confidence: 74%
“…[13][14][15][16] Previous work showed that rat HSCs express glutamine synthetase leading to our hypothesis that excess ammonia may therefore produce deleterious effects on the activity and function of primary human HSC as it does in astrocytes. [17] Following acute or chronic liver injury, HSCs undergo phenotypic transformation from "quiescent" (non-proliferating and non-contractile) to "activated" (promitogenic, [28,29] in BDL rats was associated with a negative modulation of HSC activation and in the reduction of portal pressure.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In line with previous data [3,17], HSC in culture spontaneously transform to myofibroblast-like cells within one week. As shown in fig.…”
Section: Cd95 Expression and Apoptosis In Cultured Hscsupporting
confidence: 76%
“…d MTX-ATRA cotreated group: individual sinusoidal dilation (arrow head) Jaskiewicz et al (1996) reported that MTX administration activates HSCs leading to liver fibrosis. On the other hand, another report mentioned that activation of HSCs converts it to myofibroblasts with subsequent loss of its retinoid storage (Abdel-Bakky et al 2011;Bode et al 1998). Results of our study showed that RXR-α and RAR-α expression is downregulated in MTX model of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 96%